The Construction of Women's Piety Through Women's Special Mushaf - Mustafa, Ahsin Dinal; Miski, Miski (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
The Cordoba Qur'an Special for Muslimah features the '319 thematic interpretations regarding women,' which is intended to 'beautify' women by making them pious women. However, the main question is what kind of 'piety' is meant. From this section, it is evident how women are made objects within it. As an interpretation, this prominent feature is never free of interest. This article aims to explain and analyze the construction of women's piety in the related mushaf and its relevance to the aspects of tafsir scholarship and the context of positioning women in life. By using explanatory and correlative analysis of the 319 thematic interpretations specifically for women in the mushaf, this article shows that women's piety is constructed through the process of thematizing Qur'anic verses according to certain understandings through titles that give a convincing impression because they contain narratives of hadith or explanations by Muslim figures. However, the relevance of these interpretations is questionable, both from the aspect of tafsir scholarship and the aspect of women's existence itself. In fact, in some examples of interpretation, certain parts are neglected, such as the context of the verses and the resulting interpretations that tend to be patriarchal. Thus, this issue cannot be ignored. It is not only related to the discourse of interpretive authority but also concerns gender justice, which deserves attention.